Foreign banks and credit stability: Evidence from Malaysia - Zakaria, R.H. (2008)
This paper aims to examine whether foreign banks lending behavior affects Malaysian credit stability. Thus far, the concern is foreign banks could potentially withdraw from host-country economy or shrink their lending base during economic downturns, leading to an unstable credit environment. Another argument claims that foreign banks lending preferences could also lead to credit segregation between them and their technology in screening loan applications enables them to have the best borrowers among potential lenders in the sense of lower probability of default as opposed to the domestic banks. Consequently, domestic banks are left with higher risk lending portfolio. Employing traditional financial ratio analysis and standard panel data lending estimation, the findings expose that in the case of Malaysia, foreign banks are credit stabilizer in the sense that their lending cyclicality nature moderated bank lending sensitivity to economic cycles and these is no evidence to claim they contracted their lending during the recent financial crisis. The case for concern, however, lies within the fact that the evidence suggests the credit segregation hypothesis holds true. Foreign banks "cherry pick" loans in the commercial and industrial sector, while their domestic counterparts lending is highly concentrated in the risky real estate loans.